Detection of bioactive compounds by using hptlc from wrightiatinctoria (r.br.) and amorphophallus campanulatus (ROXB.) - BHAGWAN M. WAGHMARE; RAHUL K. DHABALE (International Journal of Pharma and Bio Sciences, 2017)
A plant always has been used as sources of medicine and play a vital role in health care system not only in India also abroad. The W. tinctoria (R.Br) and A. campanulatus (Roxb.) highly medicinal and has been reported the presence of bioactive compounds. This paper concentrates on an important of ethno-medico point of view and due to their phytochemical activities of fruit of W. tinctoria (R.Br) and corm of A. campanulatus (Roxb.). It has been regarded to the presence of Bioactive compounds which were determined by using HPTLC techniques for detection with methanol, petroleum ether and ethyl acetate fruit extracts of W. tinctoria (R.Br) and corm of A. campanulatus (Roxb.). The results are notable, different separation pattern was observed. The Bioactive compound separated at Rf values 0.37 (±0.02) and 0.51 (±0.02) were found with characteristic colour reaction by anisaldehyde sulphuric acid reaction. The isolated compounds are determined and identified as beta-sitosterol, lupeol from fruit and corm extracts of W. tinctoria (R.Br) and A. campanulatus (Roxb.) respectively.